2020
DOI: 10.1002/smi.2967
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, infertility‐related stress and quality of life in women undergoing an assisted reproductive treatment

Abstract: The investigation of the association between alexithymia and quality of life in infertility is a relatively neglected area of research. The aim of this study was to evaluate the association between alexithymia and infertility-related quality of life in women during Assisted Reproductive Treatment. Data were collected in a clinic in Rome, 93 infertile women completed the 20-item Toronto Alexithymia Scale (TAS-20), the Fertility Quality of Life (FertiQoL) questionnaire and a socio-demographic questionnaire. TAS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
2
16
1
Order By: Relevance
“…In other words, difficulty in emotional awareness at first and then a low level of self-esteem in sexual function can decrease adjustment and increase stress in marital relationships. This finding is consistent with some previous research (Gourounti et al, 2016;Renzi et al, 2020;Falahati & Mohammadi, 2020;Rajabi et al, 2015;Omidi & Talighi, 2017;Tavakolizadeh & Rastgoo Nejad, 2016;Zayed & El-Hadidy, 2020;Hwang, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In other words, difficulty in emotional awareness at first and then a low level of self-esteem in sexual function can decrease adjustment and increase stress in marital relationships. This finding is consistent with some previous research (Gourounti et al, 2016;Renzi et al, 2020;Falahati & Mohammadi, 2020;Rajabi et al, 2015;Omidi & Talighi, 2017;Tavakolizadeh & Rastgoo Nejad, 2016;Zayed & El-Hadidy, 2020;Hwang, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The initial finding of this study support that alexithymia and difficulty in emotional awareness have negative influences on the adjustment and stress level of infertile women in their marital relationship. This result is consistent with previous studies approving the relationship between alexithymia and marital psychological problems (Gourounti et al, 2016;Renzi et al, 2020;Falahati and Mohammadi, 2020;Rajabi et al, 2015;Omidi & Talighi, 2017). There is no doubt that infertility and its treatment process are so stressful, and infertile women suffer from shame, guilt, anger, sadness, and loss of control.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Men are more likely to suppress painful and negative emotions, defending themselves from depression and depression-like symptoms ( Conrad et al, 2001 ). On the other hand, alexithymia measured on infertile women undergoing in-vitro treatments was associated with maladaptive coping strategies and psychological stress ( Gourounti et al, 2016 ) further considered as a risk factor for symptoms of anxiety, depression, psychological distress ( Juriü Vukeliü et al, 2019 ), and reduced quality of life ( Renzi et al, 2020a , 2020b ). Moreover, alexithymia also results as predictive of greater body checking and body dissatisfaction as compared to non-alexithymic women ( De Berardis et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the ART context specifically, a recent study (Renzi et al, 2020a(Renzi et al, , 2020b showed that, among women undergoing ART, higher attachment avoidance predicted poorer ART outcome, explaining that such relation might be given by the negative consideration that avoidant individuals have of others and the related reduced tendency to seek external support. As such, the authors continued hypothesizing that this could then lead to heighten stress hindering ART outcome.…”
Section: Introductionmentioning
confidence: 99%